2021
DOI: 10.3390/cancers13205037
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Reactive Oxygen Species in Colorectal Cancer: Involved Processes and Therapeutic Opportunities

Abstract: Colorectal cancer (CRC) is the fourth most common cause of cancer deaths worldwide. Although screening programs have reduced mortality rates, there is a need for research focused on finding the main factors that lead primary CRC to progress and metastasize. During tumor progression, malignant cells modify their habitat, corrupting or transforming cells of different origins and creating the tumor microenvironment (TME). Cells forming the TME like macrophages, neutrophils, and fibroblasts generate reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 158 publications
0
27
0
Order By: Relevance
“…Neutrophil oxidative burst has been reported to promote tumor progression [ 17 ]. As shown in Figure 3 a, an increase in intracellular ROS levels was detected in dHL60 cells treated with A375 CSC–CM.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophil oxidative burst has been reported to promote tumor progression [ 17 ]. As shown in Figure 3 a, an increase in intracellular ROS levels was detected in dHL60 cells treated with A375 CSC–CM.…”
Section: Resultsmentioning
confidence: 99%
“…Many chemotherapeutic agents act as DNA damage inducers, leading to cancer cell death. Inactivation of GSTs often induces ROS production that causes DNA damage ( 29 ). However, chemotherapeutic agents may also modulate GST expression and ROS production ( 5 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…The tumor microenvironment is enriched with ROS that have multifaceted roles in cancer cell proliferation, apoptosis, angiogenesis, and metastasis ( 29 ). GSTs, as anti-oxidant enzymes, can eliminate ROS and protect cells against ROS-induced apoptosis ( 5 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on basic tumor biology have shown that the tumor microenvironment (TME) plays a vital role in remodeling metastatic capacity and determining tumor prognosis (10)(11)(12). Cancer-associated fibroblasts (CAFs) are the major cellular components of the TME and have recently been regarded as critical factors to modulate the TME (13,14).…”
Section: Introductionmentioning
confidence: 99%